Embedding Character Education Through Citizenship Education in Elementary Schools - Rizal Nugraha; Reinald Fahrezzi; Mochamed Hildan Praja (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Citizenship education is one of the right tools to implement values in student character education, because civic education is essentially to form citizens of students who are democratic and have characters that are in accordance with the values of Pancasila. The purpose of this study was to determine the character of students in schools through civics education, the character of students needs to be built from an early age as a provision for the next generation of young people. The benefit of this research is to create students to become citizens who are democratic and have character according to the values of Pancasila. The method used in this study uses qualitative methods, namely research that is descriptive and tends to use analysis. Character education is very important, especially in relation to civics education because civics education can be formed through learning and developing the character of elementary school students.